Matching language proficiency to occupation: the effect on immigrants' earnings - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2007)
This paper analyzes the effect on earnings of the matching of English language skills to occupational requirements. It uses data from the Occupational Information Network (O*NET) database and a Realized Matches procedure to quantify expected levels of English skills in each of over 500 occupations in the US Census. Earnings data from the 2000 US Census for foreign-born adult male workers are then examined in relation to these occupational English requirements. The analyses show that earnings are related to correct matching of an individual's language skills and that of his occupation. Moreover, the findings are robust with respect to a range of measurement and specification issues. Immigrant settlement policy may have a role to play in matching immigrants to jobs that use their language skills most effectively
urn:nbn:de:101:1-2008042579
Keywords: 330; Migranten; Sprache; Qualifikation; Humankapital; Beruf; Lohnstruktur; USA